Natural Cyclooxygenase-2 Inhibitors Synergize With Butyrate to Augment Chicken Host Defense Peptide Gene Expression - Yang, Qing; Burkardt, Amanda C.; Sunkara, Lakshimi T.; Xiao, Kan; Zhang, Guolong (Frontiers in Immunology, 2022)
Enhancing the synthesis of microbicidal and immunomodulatory host defense peptides (HDP) is a promising host-directed antimicrobial strategy to combat a growing threat of antimicrobial resistance. Here we investigated the effect of several natural cyclooxygenase-2 (COX-2) inhibitors on chicken HDP gene regulation. Our results indicated that phenolic COX-2 inhibitors such as quercetin, resveratrol, epigallocatechin gallate, anacardic acid, and garcinol enhanced HDP gene expression in chicken HTC macrophage cell line and peripheral blood mononuclear cells (PBMCs). Moreover, these natural COX-2 inhibitors showed a strong synergy with butyrate in augmenting the expressions of multiple HDP genes in HTC cells and PBMCs. Additionally, quercetin and butyrate synergistically promoted the expressions of mucin-2 and claudin-1, two major genes involved in barrier function, while suppressing lipopolysaccharide-triggered interleukin-1β expression in HTC macrophages. Mechanistically, we revealed that NF-κB, p38 mitogen-activated protein kinase, and cyclic adenosine monophosphate signaling pathways were all involved in the avian β-defensin 9 gene induction, but histone H4 was not hyperacetylated in response to a combination of butyrate and quercetin. Because of their HDP-inducing, barrier-protective, and antiinflammatory activities, these natural COX-2 inhibitors, when combined with butyrate, may be developed as novel host-directed antimicrobial therapeutics.